The Cambridge companion to British literature of the French Revolution in the 1790s - Clemit, Pamela (Cambridge companions to literature, 2011)
"The French Revolution ignited the biggest debate on politics and society in Britain since the Civil War 150 years earlier. The public controversy lasted from the initial, positive reaction to French events in 1789 to the outlawing of the radical societies in 1799. This Cambridge Companion highlights the energy, variety and inventiveness of the literature written in response to events in France and the political reaction at home. It contains thirteen specially commissioned essays by an international team of historians and literary scholars, a chronology of events and publications, and an extensive guide to further reading. Six essays concentrate on the principal writers of the Revolution controversy: Burke, Paine, Godwin and Wollstonecraft. Others deal with popular radical culture, counter-revolutionary culture, the distinctive contribution of women writers, novels of opinion, drama, and poetry. This volume will serve as a comprehensive yet accessible reference work for students, advanced researchers and scholars"--